The Effects of Unconventional Financing on the Algerian Economy An Evaluation Study during the Period (2017-2019) - Bahloul, Noureddine (Milev Journal of Research and Studies, 2023)
The researchers aim through this research paper to highlight the effects left by unconventional financing approved by the Algerian government, and this strategic choice of the government came in exceptional circumstances through which the national economy, embodied in the sharp decline in oil prices starting from mid-2014 has had a significant impact on Public finance, which led to the rapid erosion of important savings in the consolidated budget during several years, in addition to the suspension of several public projects that were under construction Consequently, this research comes to throw more analysis and discussion about the effects of this type of financing, and the measures that must be taken in the future to avoid them, and for this there were many scientific and field results, the most important of which was that unconventional financing is an effective financial tool for countries to get out of some financial crises If properly used, the adverse effects of it must be faced and price stability ensured in an excess liquidity environment